Rehabilitation experience in a case of Ollier’s disease - Formis, A.; Allegri, S.; Posterano, L. (Acta Biomedica Atenei Parmensis, 2003)
This paper describes a case of Ollier’s disease, an uncommon, nonhereditary skeletal disorder affecting enchondral ossification. The patient was referred to our Rehabilitation Unit after resection of scapular chondroma. He had previously been submitted to several surgical treatments for multiple enchondromatosis. Rehabilitation goals were increasing range of motion, relieving pain and training activities of daily living (ADL). After one month treatment, the patient reported pain relief and showed good improvement of articular function and better performances on ADL. According to our experience, it seems that rehabilitation could play a complementary role as regards surgical treatment of this complex pathology.